Mycobacterium tuberculosis lipoproteins in virulence and immunity – fighting with a double‐edged sword. Issue 21 (13th July 2016) - Becker, Katja; Sander, Peter
Abstract : Bacterial lipoproteins are secreted membrane‐anchored proteins characterized by a lipobox motif. This lipobox motif directs post‐translational modifications at the conserved cysteine through the consecutive action of three enzymes: Lgt, LspA and Lnt, which results in di‐ or triacylated forms. Lipoproteins are abundant in all bacteria including Mycobacterium tuberculosis and often involved in virulence and immunoregulatory processes. On the one hand, disruption of the biosynthesis pathway of lipoproteins leads to attenuation of M. tuberculosis in vivo, and mycobacteria deficient for certain lipoproteins have been assessed as attenuated live vaccine candidates. On the other hand, several mycobacterial lipoproteins form immunodominant antigens which promote an immune response. Some of these have been explored in DNA or subunit vaccination approaches against tuberculosis. The immune recognition of specific lipoproteins, however, might also benefit long‐term survival of M. tuberculosis through immune modulation, while others induce protective responses. Exploiting lipoproteins as vaccines is thus a complex matter which requires deliberative investigation. The dual role of lipoproteins in the immunity to and pathogenicity of mycobacteria is discussed here. Abstract :